The use of the cognitive-behavioral therapy model in the psychological assistance of emotional disorders in adolescents. Case study / Utilizarea modelului terapiei cognitiv-comportamentale în asistența psihologică a tulburărilor emoționale la adolescenți. Studiu de caz - CALANCEA Angela (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
At the ever-increasing pace, imposed by the conditions of present life, of the struggle for existence that is becoming fiercer, the demands that arise on the personality are more and more numerous. The personality must face obstacles, overcome frustrations, or overcome inconvenient situations. This is exacerbated at this stage by the fact that the value and content orientations have become more diffuse and the personality, especially that of the adolescent, is increasingly prone to disorders of the emotional, mental, cognitive, and behavioral spheres. All this imposes a new vision on the emotional adaptation of contemporary adolescents. In this order of ideas, we focused the scientific investigation on the specifics of the affective sphere of adolescents, capitalizing on the theoretical-experimental models that aim at the discussed issue, complementing it with new data. The study of emotional disorders as well as the use of the behavioral cognitive therapy model reduces the symptoms of depression, generalized anxiety and social anxiety in adolescents.